Kehematan Kalimat Pada Judul Artikel Tugas Mata Kuliah Kapita Selekta Dengan Model Portofolio - Khusnul Khotimah; Syamsul Anwar (Universitas Pancasakti Tegal, 2018)
The Kapita Selekta course is a course that is intended for fifth semester students (five). The course is a very complex subject because the content and essence of the course discusses all in Indonesian. The purpose of this study is to describe the pattern of making semi-scientific article titles in the Indonesian language course and to describe the economics of making titles in semi-scientific articles on Kapita Selekta courses in the 5th semester of the Indonesian Education Study Program at the Pancasakti University in Tegal.Based on the analysis carried out there are results that have been presented, namely the element of economics which includes four aspects which can be seen from the percentage that has been calculated. Aspect of misinformation 40%, superordinate hypernim 32%, plural words 24% and repetition of subjects 4%. It is seen that those who occupy the element of non-health in the title of semi-scientific articles in the Indonesian selective course, namely aspects of the use of synonyms, occur because the author wants to emphasize the idea that the titles written or chosen can attract readers, but because synonymy and diction are lacking accordingly it should be avoided, for the good of the reader in understanding the reading title.